IMPACT OF PARENTAL GUIDANCE ON MORAL DEVELOPMENT OF ADOLESCENTS IN LOKOJA, KOGI STATE: COUNSELLING IMPLICATION - AMADI, Glory, E. (Journal of Professional Counselling, 2025)
This study investigated the impact of parental guidance on the moral development of adolescents in Lokoja, Kogi State and its counselling implications. The primary goal was to assess how parental guidance impacts adolescents' moral reasoning, ethical decision making, and general moral development through open communication, role modelling, and the establishment of clear moral expectations. The study used descriptive survey research. Out of a 396,337 population, 400 JSS1-JSSIII adolescents from six secondary schools were purposively selected for the study. "The Impact of Parental Guidance on Moral Development of Adolescents in Lokoja, Kogi State Questionnaire" was a carefully developed questionnaire used for data collection with a reliability coefficient of 0.87 using Cronbach Alpha. Data analysis used the Chi-square (χ2) test at a 0.05 significance level. The findings revealed that the development of adolescents' moral reasoning, ethical decision-making, and overall moral character were all positively correlated with parental guidance, which includes open communication, parental role modelling, and the establishment of clear moral expectations. This proved that adolescents who get regular positive parental guidance exhibit higher levels of moral awareness, empathy, and social conformity, whereas lack of parental guidance or negative guidance leads to moral disengagement and bad conduct. The study suggested that family-based strategies can enhance moral guidance in adolescents, highlighting the importance of parental impact on adolescent moral development. Implications for counsellors include the need to design programs that teach parents effective guidance skills and encourage cooperation between counsellors, parents, and adolescents to improve moral development.